Kualitas Nutrisi Silase Berbahan Baku Singkong yang Diberi Enzim Cairan Rumen Sapi dan Leuconostoc mesenteroides - S Sandi; E B Laconi; A Sudarman; K G Wiryawan; D Mangundjaja (Media Peternakan, 2010)
The aim of this experiment was to evaluate the nutrient quality of cassava-based materials silage with cattle rumen liquor enzymes and Leuconostoc mesenteroides as poultry feed. The cassava material was hydrolyzed with cattle rumen liquor enzyme and incubated for 24 hours. The hydrolyzed product was added L. mesenteroides and ensiled in mini silo for 30 days. The experiment was designed in completely randomized design with 15 treatments and 3 replications. The result showed that temperature of cassava-based silage ranged from 26 to 30 oC. The flavor was sour and fresh fragrant and changed in color. Addition of cattle rumen liquor enzyme and L. mesenteroides bacteria significantly affected (P < 0.05) pH (3.73-4.86), dry matter(30.14%-43.28%), cyanide (86.71%-96.50%) and crude fiber content (0.78%-5.05%), but gave a fluctuate effect on protein content (-1.92%-2.39%). However, the treatment didnot affect dry matter losses (1.20%-2.66%). It is concluded that nutrient quality of cassava-based silage improved when it was added with cattle rumen liquor enzymes and L. mesenteroides by decreasing crude fiber and cyanide content. The best silage quality was obtained on tuber substrate and it increased protein KDUO (peel+leaves+tuber+tapioca waste) silage.   Key words: cassava-based silage, cattle rumen liquor enzymes, Leuconostoc mesenteroides, nutrient quality